2021
DOI: 10.1038/s41467-020-20720-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmons in the van der Waals charge-density-wave material 2H-TaSe2

Abstract: Plasmons in two-dimensional (2D) materials beyond graphene have recently gained much attention. However, the experimental investigation is limited due to the lack of suitable materials. Here, we experimentally demonstrate localized plasmons in a correlated 2D charge-density-wave (CDW) material: 2H-TaSe2. The plasmon resonance can cover a broad spectral range from the terahertz (40 μm) to the telecom (1.55 μm) region, which is further tunable by changing thickness and dielectric environments. The plasmon disper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 68 publications
5
23
0
Order By: Relevance
“…A previous study reported that the SPR of TaSe 2 mainly occurs in the terahertz and telecom range. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that the SPR of TaSe 2 mainly occurs in the terahertz and telecom range. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that the SPR of TaSe 2 mainly occurs in the terahertz and telecom range. [23] The SERS mechanism can be described using a polarization tensor equation: α = A + B + C, in which A denotes the molecular resonance and B and C represent the SPR and molecule-metal charge-transfer resonance at the Fermi level, respectively. [56] The SPR effect is excluded in this paper.…”
Section: Sers Mechanism Of Tasementioning
confidence: 99%
See 1 more Smart Citation
“…The plasmon dispersion is obtained from the dynamical dielectric function tensor i.e. ε(q, ω) which is written in terms of the optical conductivity tensor using the following relation for free-standing 2D materials 24,95,96 εðq i ; ωÞ ¼ 1 þ j2πq i σ ii ðωÞ=ω; i ¼ x; y:…”
Section: Anisotropic Propagation Aspectsmentioning
confidence: 99%
“…In 2D material (2DM) plasmonics, graphene/hBN and hBN/graphene/hBN are the most studied vdW heterostructures [23][24][25] because of high carrier mobilities [26] and easy control of the spectral range of interest (from mid-infrared to visible) by means of gate voltage. However, multitude of two-dimensional materials discovered for the past decade, open up new possibilities [27].…”
Section: Introductionmentioning
confidence: 99%